Persepsi Pengguna QRIS Pada UMKM Di Kota Mataram - Aryawati, Ni Putu Ari; Mahardika, I Made Ngurah Oka; Wibawa, I Gede Jaya Satria (Guna Sewaka, 2022)
This study discusses the role and perspection of QRIS in transactions at MSMEs in Mataram City. Qris is a new innovation which launched by Bank Indonesia on 74th Independence Day. QRIS as a standardization of non-cash payments based on QR Code as a unifier of non cash payments. This study use a descriptive qualitative approach. Locus of this research is located at MSMEs assisted in Mataram City. The data were obtained using an interview and documentation approach with non-participatory observation. This study found that QRIS be a supportive payment tools of transactions in MSMEs but many people do not understand about QRIS. The solution that can be used so that many people know about QRIS is by socializing it to the community and leading MSMEs to use QRIS. QRIS can help MSMEs move forward in line with progress in the current digital era, QRIS has many important roles and many benefits for MSMEs, judging by the development and progress of the current digital era, it makes it easier for consumers and sellers to buying and selling transactions.